Citrullination enhances the pro-inflammatory response to fibrin in rheumatoid arthritis synovial fibroblasts. Issue 8 (12th December 2012) - Sanchez-Pernaute, Olga; Filkova, Maria; Gabucio, Antonio; Klein, Martin; Maciejewska-Rodrigues, Hanna; Ospelt, Caroline; Brentano, Fabia; Michel, Beat A; Gay, Renate E; Herrero-Beaumont, Gabriel; Gay, Steffen; Neidhart, Michel; et al.
Abstract : Objective: Fibrin deposits are characteristic of the synovial tissues in rheumatoid arthritis (RA). Once citrullinated, fibrin becomes an autoantigen and is thought to contribute in this way to perpetuate the disease. Our study aimed to analyse the responses of RA synovial fibroblasts (RASF) to native and citrullinated fibrin. Methods: The transcriptome induced by fibrin in RASF was approached with whole-genome-based gene expression arrays. The upregulation of selected pro-inflammatory genes by fibrin was confirmed in additional primary cell cultures using quantitative PCR and ELISA. Citrullination reactions were carried out with recombinant human peptidylarginine deiminases (PAD) 2 and 4. Results: In the whole-genome array native fibrin was found to modulate the gene expression profile of RASF, particularly upregulating mRNA levels of several pro-inflammatory cytokines. The induction of interleukin (IL)-6 and IL-8 by fibrin was confirmed in additional samples at both the mRNA and the protein level. Blocking and knockdown experiments showed the participation of toll-like receptor (TLR)4 in the induction of both cytokines. As compared with the native macromolecule, PAD2-citrullinated fibrin induced significantly higher expression of the pro-inflammatory cytokines in these cells. Conclusions: Our results suggest that fibrin mediates inflammatory responses in RASF via a TLR4 pathway. In this way, fibrin and particularly its citrullinated form may contribute to sustain the cytokine burst in RA.